2017
DOI: 10.3390/nano7120418
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and Flexible Capacitors with an Ultrathin Structure by Using Graphene as Bottom Electrodes

Abstract: Ultrathin, transparent and flexible capacitors using graphene as the bottom electrodes were directly fabricated on polyethylene naphthalate (PEN) substrates. ZrO2 dielectric films were deposited on the treated surface of graphene by atomic layer deposition (ALD). The deposition process did not introduce any detectible defects in the graphene, as indicated by Raman measurements, guaranteeing the electrical performances of the graphene electrodes. The Aluminum-doped zinc oxide (AZO) films were prepared as the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Reduced graphene oxide (rGO) is a high-temperature resistant and environmentally friendly material with a melting point of over 4000 K [13]. It shows important application prospects in advanced materials science [14], new energy and biomedicine, and is considered to be a revolutionary material [15] for the future, making it a current research hotspot. Huang et al prepared polyvinyl alcohol/rGO nanocomposites by a solution blending method, and the results showed that the composite materials burned to form a dense and uniform carbon layer, which can prevent the thermal mass transfer and exchange of the combustible gas between the matrix material and the outside [16].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced graphene oxide (rGO) is a high-temperature resistant and environmentally friendly material with a melting point of over 4000 K [13]. It shows important application prospects in advanced materials science [14], new energy and biomedicine, and is considered to be a revolutionary material [15] for the future, making it a current research hotspot. Huang et al prepared polyvinyl alcohol/rGO nanocomposites by a solution blending method, and the results showed that the composite materials burned to form a dense and uniform carbon layer, which can prevent the thermal mass transfer and exchange of the combustible gas between the matrix material and the outside [16].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, our work shows the highest capacitance density and k-value with comparably low leakage current density level (10 −7 A cm −2 ) and decent flexibility (10 mm radius convex bending) compared with other flexible capacitors ever fabricated by ALD techniques and other low-temperature processes directly on flexible substrates including PET, PEN, PI, and PC (Table 1). [39][40][41][47][48][49][50][51] Generally, the flexible capacitor with ALD-processed dielectric layers showed higher capacitance density. For example, Zhang et al [39] fabricated flexible MIM capacitors with a surface area enhancing regime by incorporating Ag NWs into the bottom electrode composite ALD-AZO (Al-doped ZnO)/Ag NWs/sputtered AZO, which exhibited a capacitance density of 10.1 nF mm −2 at 10 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, our work shows the highest capacitance density and k ‐value with comparably low leakage current density level (10 −7 A cm −2 ) and decent flexibility (10 mm radius convex bending) compared with other flexible capacitors ever fabricated by ALD techniques and other low‐temperature processes directly on flexible substrates including PET, PEN, PI, and PC ( Table 1 ). [ 39–41,47–51 ] Generally, the flexible capacitor with ALD‐processed dielectric layers showed higher capacitance density. For example, Zhang et al.…”
Section: Resultsmentioning
confidence: 99%
“…More researches have been published on metal-insulator-metal capacitors using ALD [198][199][200][201]. More work on the application of ALD for capacitors has been done by different researchers looking at the growth rate, limitations and various applications on different materials [202][203][204][205][206][207]. Figure 8.…”
Section: Capacitorsmentioning
confidence: 99%